2020
DOI: 10.1186/s13023-020-01409-5
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial lung biopsy for the diagnosis of lymphangioleiomyomatosis: the severity of cystic lung destruction assessed by the modified Goddard scoring system as a predictor for establishing the diagnosis

Abstract: Background A guide of patient selection for establishing the diagnosis of lymphangioleiomyomatosis (LAM) by transbronchial lung biopsy (TBLB) has not been established, although the pathological confirmation of LAM by lung biopsy is desirable, particularly when patients have no additional test results except typical findings of computed tomography (CT) of the chest. Methods We retrospectively reviewed the medical records of LAM patients who visited at our hospital from January 2010 to September 2018. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
2
8
1
Order By: Relevance
“…Our results offered similar experience of the value of TBLB in LAM. The positive rate of TBLB in our results was similar to those previously reported [ 5 , 6 , 12 ]. In addition, the complications of TBLB were also similar to previous reports.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results offered similar experience of the value of TBLB in LAM. The positive rate of TBLB in our results was similar to those previously reported [ 5 , 6 , 12 ]. In addition, the complications of TBLB were also similar to previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…found that TBLB was positive in 6 of 10 patients and had a yield of approximately 60% in LAM, with 52/217 (14%) complications, including pneumothorax (6%), bleeding (4%), chest pain (2%) and pneumonia (2%) [ 11 ]. In recent years, some researchers reported that the positive rate of TBLB in patients with LAM was 70–78%, and there were no serious adverse events such as pneumothorax or uncontrollable bleeding due to TBLB [ 5 , 6 ]. Our results offered similar experience of the value of TBLB in LAM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the experience of this application has seldom been reported since the publication of this recommendation (5,6). We aimed to report our experience using TBLB on patients at the LAM Clinic in Peking Union Medical College Hospital (PUMCH), Beijing, China.…”
Section: Introductionmentioning
confidence: 99%